Model Permintaan Pekerjaan - Sumber Daya Untuk Kesejahteraan Dan Produktivitas Karyawan - Nisa Nur Aini; Barkah Rosadi; Muhammad Yusuf Alhadihaq (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Employee well-being is an important factor for individuals and to ensure company sustainability. The research objective is to develop a Job Demand-Resources (JD-R) model that can predict employee well-being and productivity at PT Fengtay Indonesia Enterprise. Explanatory survey of 250 randomly selected non-manager employees of PT Fengtay Indonesia Enterprise. Inferential analysis using SEM with SPSS25 tools. The results of the study show that job demands, such as high task demands and tight time pressure, have a negative and significant relationship with employee welfare, while job resources, such as social support from colleagues and superiors, have a positive and significant effect on employee well-being. ultimately increase productivity. The proposed JD-R model can be a useful tool for human resource management in developing effective strategies to improve employee welfare and individual productivity. The JD-R model helps managers to improve employee well-being and productivity. Management can ensure support to employees thereby increasing their well-being and productivity. Keywords: Job demand, Job Resources, Productivity, well-being, textile manufacturing